2023
DOI: 10.1002/we.2847
|View full text |Cite
|
Sign up to set email alerts
|

Copula‐based joint distribution analysis of wind speed and wind direction: Wind energy development for Hong Kong

Abstract: Accurate and reliable assessment of wind energy potential has important implication to the wind energy industry. Most previous studies on wind energy assessment focused solely on wind speed, whereas the dependence of wind energy on wind direction was much less considered and documented. In this paper, a copula‐based method is proposed to better characterize the direction‐related wind energy potential at six typical sites in Hong Kong. The joint probability density function (JPDF) of wind speed and wind directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It is mainly used to model the joint distribution function of random variables, which separates the marginal distribution from dependence and makes the model more flexible. There are various types of copula functions, and the common ones include Gaussian copula [41], t-distribution copula [42], Clayton copula [43], and Frank copula [44]. Each type of copula corresponds to a different dependence structure, so choosing an appropriate copula function is crucial for accurately describing the dependence among variables.…”
Section: Theory Of Two-dimensional Copula Functionsmentioning
confidence: 99%
“…It is mainly used to model the joint distribution function of random variables, which separates the marginal distribution from dependence and makes the model more flexible. There are various types of copula functions, and the common ones include Gaussian copula [41], t-distribution copula [42], Clayton copula [43], and Frank copula [44]. Each type of copula corresponds to a different dependence structure, so choosing an appropriate copula function is crucial for accurately describing the dependence among variables.…”
Section: Theory Of Two-dimensional Copula Functionsmentioning
confidence: 99%
“…Li et al [ 31 ] demonstrated that the copula approach is superior in binary distributions adjustment of wind speed and direction, as well as in predicting extreme wind speeds, through a comparison of its performance with that of conventional methods. Huang et al [ 32 ] evaluated the directional wind energy potential in Hong Kong based on various copula functions.…”
Section: Introductionmentioning
confidence: 99%